COMPARISON OF TOPICAL CAPSAICIN AND TOPICAL TURPENTINE OIL FOR TREATMENT OF PAINFUL DIABETIC NEUROPATHY - Musharraf, Muhammad Usman; Ahmad, Zaheer; Yaqub, Zernab (Journal of Ayub Medical College Abbottabad, 2017)
Background: Diabetes Mellitus is a pandemic of the modern era owing to our rapidly deteriorating lifestyle. Painful diabetic neuropathy is one of the costliest and disabling complications of diabetes mellitus. No single treatment exists to prevent or reverse neuropathic changes or to provide total pain relief. Topical Capsaicin and Turpentine Oil are found to be effective in treatment of painful diabetic neuropathy. Methods: Patients of either gender with ages between 18 and 70 years having painful diabetic neuropathy already taking one oral drug for painful neuropathy and treatment for diabetes mellitus and an HbA1C less than 8.5% were included while Pregnant or lactating mothers, patients with chronic liver disease and patients with renal insufficiency (creatinine >3.0 mg/dl) and peripheral arterial disease were excluded from study. Patients were randomly divided into two groups (A & B) using computer generated random number table. Group A was given topical application of capsaicin while Group B was given topical application of commercially available turpentine oil over painful site on feet. Results: 300 patients were equally divided in two groups. The patients in group A had a Visual Analog Pain Score of 7.91±5.10 at baseline and 5.10±1.343 after 3 months of treatment (p-value 0.0001). The patients in group B had a Visual Analog Pain Score of 7.83±1.012 at baseline and 5.20±1.187 after 3 months of treatment (p-value 0.0001). Chi Square test was applied to compare efficacy of both groups. It was noted that 71 (53%) had efficacy in group A and 63 (47%) had efficacy in the group B but the difference was not statistically significant. (p-value=0.399). Conclusion: It has been concluded that turpentine oil is effective in managing diabetic neuropathic pain similar to capsaicin cream. Keywords: Diabetes Mellitus; Painful diabetic neuropathy; Capsaicin; Turpentine oil